A Model the Facility Management With Electricity Saving of the Personnel in Primary Schools - Sriwichaimun, Yutthapong; Poovatanakul, Vipaporn; Nirunthawee, Sakchai; Meekun, Kossol; Plangklang, Boonyoung (Mahachula Academic Journal, 2024)
The purposes of this research were to (1) study the condition of building management to enhance electricity saving behavior of the personnel in primary schools, (2) develop a building management model to enhance electricity saving behavior of the personnel in elementary schools and(3) evaluate the effectiveness of the building management model to enhance electricity saving behavior among personnel in elementary schools, There were 30 school personnel of the experimental group and 30 school personnel of the control group. The research tools were interview forms, examination forms, assessment forms and questionnaires. Data were analyzed by using descriptive statistics, mean standard deviation and t-test. The results showed that (1) The conditions of building management of the experimental group and the control group using the POSDCoRB theoretical process were similar to electrical equipment and electricity cost because they were in the same district and also they had the similar context of energy saving management, and the same behavior problem of electric equipment using of personnel in both schools. (2) The result of the development of a building management Model to Enhance Electricity Saving Behavior model was Model to Enhance Electricity Saving Behavior (BPAOR Model). (3) In addition the results of the evaluation of the effectiveness of the building management model to enhance energy saving behavior of school personnel were as follows: (3.1) The experimental group had move knowledge about energy saving than that of the control group with statistically significant level at .05,. (3.2) The experimental group after using the model had higher performance than that of the control group (Post) higher, with statistically significant level at .05, and It also found that the follow up results on energy saving behavior of experimental group were higher than that of the group did not use the model activity with significantly at .05, and (3.3) The satisfaction assessment result of school personnel towards the overall model was found to be at the highest level.